Analysis of Factors Affecting the Price of Maize as Animal Feed in Tigabinanga District, Karo Regency - R F Andrean; R E Mirwandoho; A H Daulay; S Manulang (Talenta Publisher, 2024)
Maize plays a vital role in the animal feed industry. Maize prices have a relationship with animal feed prices, especially for poultry. The objective of the study was to determine the marketing channel of maize, maize production, and factors affecting the price of maize as an animal feed ingredient. This study was conducted in Tigabinanga sub-district, Karo district, as the largest contributor to maize production in North Sumatra. The research used snowball sampling method. The total number of respondents in this research was 30 respondents. The results showed that farmers have 3 maize marketing channels in the study area. Total maize production is 2,556 tonnes/month, with an average of 85.2 tonnes/respondent/month. Factors that partially influence the price of maize as an animal feed ingredient are maize sales Kg/period (X1), seed price Rp/Kg (X2), and fertiliser price Rp/Kg (X3). In conclusion that there are three marketing channels that work together and the first channel isÂ farmers distribute to agents/small traders. The next channel is from small traders/agents to collectors. The collectors then market to individual storage warehouses.